The Effect of the TGT Learning Model Assisted by One-Sided Flashcards on the Cognitive Domain Assessment Results of Seventh Grade Students in Fiqh at MTs Sumbersari Kowang - Hasanah, Rofi’atul; Ana Achoita (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The purpose of this study was to analyze the effect of the Teams Games Tournament (TGT) cooperative learning model, supported by One-Sided Flashcards, on students' cognitive domain assessment results in the seventh-grade Islamic Jurisprudence (Fiqh) subject. The background of this study stems from the low level of active student participation in the learning process, which tends to be one-way and lacks variety. Using a quantitative approach, this study employed a One Group Pretest-Posttest Design. The subjects consisted of seventh-grade students at MTs Sumbersari Kowang, with data collection techniques including questionnaires, tests, and documentation. Data analysis was conducted using t-tests and Pearson correlations. The results showed a significant improvement in cognitive assessment results after implementing the One-Sided Flashcard-assisted TGT model, with a significance value of <0.001. The Pearson correlation of 0.0471 indicates a fairly strong relationship, and the effect size of 2.85 indicates a high influence. Thus, the use of the TGT model, supported by visual media, has proven effective in supporting students' cognitive learning outcomes in Fiqh.